NILAI SPIRITUALISME DALAM NOVEL TARIAN DUA WAJAH KARYA S. PRASETYO UTOMO : KAJIAN SOSIOLOGI SASTRA - Candra, Nova Rian (2017)
Literary works are a reflection of life, including human life as social creature. One of them is contained in the novel Tarian Dua Wajah by S. Prasetyo Utomo which discusses the value of spiritualism in social life, especially in Cirebon community as the background of the main place of events that show the concept of spiritual values of the characters. This study uses the theory of literary sociology as a study that discusses the text of literature as a social document or as a mirror of social life of society. This study aims to (1) Analyze the novel structure of Tarian Dua Wajah (2) the spiritualism values contained in the novel (3) Factors that cause Spiritualism. By using descriptive method the source of this research is the text of Tarian Dua Wajah novel which published in 2016. Technique to collect the data is using literature study. Through this research was found three forms of concept of spiritualism value; (1) transcendent dimension with the relation of belief to the spirits experienced on the character; Aya, Mother Goddess Lakshmi, citizen who worship Nyai Laras, Mute Women, Goddess Dewi Laksmi, and Mandor Karso. Then the concept of the transcendent dimension by believing in God, is in character; Kiai Sodik, Salma, Nyai Sodik, Kiai Jangkung, Sukro, and, Aji. Next is the concept of spiritualism (2) Meaning and Purpose of Life, which occurred on the events of Aji and Sukro. The last, is the spiritual concept (3) The sacredness of life experienced by figures Aji and Coastal Coasters. The factors that cause the concept of spiritualism is in the character (1) family includes the figure Kiai Sodik, Salma, Nyai Sodik. (2) Ethnic and Cultural Backgroud includes the figure of the villagers who worships Nyai Laras. (3) Previous Life Experience includes Sukro, Mandor Karso, Aji, Astini. (4) and Developmental Stage is Dewi Laksmi.------ Karya sastra merupakan cerminan kehidupan, termasuk kehidupan manusia sebagai makhluk sosial. Salah satunya yaitu yang terdapat dalam novel Tarian Dua Wajah karya S. Prasetyo Utomo yang membahas tentang nilai spiritualisme di kehidupan sosial, khususnya di masyarakat Cirebon sebagai latar tempat utama terjadinya peristiwa yang menunjukan konsep nilai spiritualisme para tokohnya. Penelitian ini menggunakan teori sosiologi sastra sebagai kajian yang membahas teks karya sastra sebagai dokumen sosial atau sebagai cermin kehidupan sosial masyarakat. Penelitian ini bertujuan untuk (1) Menganalisis struktur novel Tarian Dua Wajah (2) Nilai-nilai spiritualisme yang terdapat dalam novel Tarian Dua Wajah (3) Faktor-Faktor penyebab Spiritualisme. Dengan menggunakan metode deskriptif sumber penelitian ini adalah teks novel Tarian Dua Wajah yang terbit 2016. Teknik pengumpulan data dengan studi pustaka. Temuan penelitian ini terdapat tiga bentuk konsep nilai spiritualisme, antara lain (1) dimensi transenden dengan hubungannya kepercayaan kepada roh-roh yang dialami pada tokoh; Aya, Bunda Dewi Laksmi, Warga pemuja Nyai Laras, Perempuan Bisu, Dewi Laksmi, dan Mandor Karso. Kemudian konsep dimensi transenden dengan percaya terhadap Tuhan, terdapat pada tokoh; Kiai Sodik, Salma, Nyai Sodik, Kiai Jangkung, Sukro, dan, Aji. Selanjutnya konsep spiritualisme (2) Makna dan Tujuan Hidup, yang terjadi pada peristiwa Aji dan Sukro. Terakhir yaitu konsep spiritual (3) Kesakralan Hidup yang dialami oleh tokoh Aji serta Warga Pesisir Pantai. Adapun faktor-faktor yang menyebabkan konsep spiritualisme terdapat pada tokoh (1) keluarga meliputi tokoh Kiai Sodik, Tokoh Salma, Tokoh Nyai Sodik. (2) Latar Belakang Etnik dan Budaya meliputi, tokoh Warga kampung pemuja nyai laras. (3) Pengalaman Hidup Sebelumnya meliputi Tokoh Sukro, Tokoh Mandor Karso, Tokoh Aji, tokoh Astini. (4) Tahap Perkembangan yaitu Tokoh Dewi Laksmi.